Javanese-Christian Church Belief and Inter-religious Dialogue - Fauzi, Maria Ulfa (DINIKA : Academic Journal of Islamic Studies, 2017)
This study attempts to elucidate both of Muslim and Christian understandings toward the idea of religious pluralism, with the case study of Javanese-Christian Church of Pogung and its relation to the surrounding community. It provides the discussion with some theological analyses on how people conceive the meaning of truth and, how this has led to the possibility and necessity of a dialogue; more specifically how their religious doctrines maintain their communities in dealing with other communities. Based on the qualitative approach, wherein the data gathered through in-depth interview and observation, the result of this study revealed that dialogue must be based on personal religious experiences and firm truth claims. Without personal religious experience, there is no way of grasping what the dialogue is all about. Dialogue must be based on the recognition of the possible truth in all religions; the ability to recognize this truth must be grounded in the hypothesis of common ground and goal for all religions. Dialogue must be based on openness to the possibility of genuine change or conversion.